Cyberbullying among Emerging Adults: Exploring Prevalence, Impact, and Coping Methods - Oblad, Timothy (International Journal of Criminology and Sociology, 2019)
Cyberbullying has been a concern among adolescents, parents and educators for years for its seemingly boundless reach and potential harm it can cause. Aggressors are often masked with anonymity and targeted individuals may feel powerless over what others do online. While such issues and concerns are prevalent among adolescent ages, college students are not invulnerable from parallel experiences. In the US, Macdonald and Roberts-Pittman (2010) found less than ten percent of college students were cyberbullies but over one-fifth reported as cybervictims. This study explored prevalence of cyber victimization and perpetration as well as evidence of damaging effects and impact. Among the college student sample of 1,921, participants were 18-25 years (mean age 20.1), just over half Caucasian (55.5%) and female (67.9%). Results indicated victimization most often occurred through phones (19.9%) and social networks (20.4%). For perpetration, prevalence was low across all platforms, however phone use was the preferred means of attacking others (6.5%). Low self-esteem was a significant predictor for victimization and perpetration. For males only, social capital was a significant predictor of victimization. Future directions and recommendations for follow-up studies are discussed as well as the importance of this study in relation to college student activities and behaviors.